Improvise the working condition at Kilang Beras Jelapang Selatan (M) Sdn. Bhd. - Tajurahim, Nurul Ainina Nadhirah; Mahmood, Salwa; Ngadiman, Nor Hasrul Akhmal (Penerbit UTHM, 2020)
Kilang Beras Jelapang Selatan (M) Sdn. Bhd. or known as KBJS was established on 11th March 1988. KBJS is located at industrial area, Batu 2 ¾ Jalan Salleh,8400, Muar, Johor. The size of the factory is more than 2.5 acre. KBJS was a Small and Medium Enterprise (SME) business owned by a Chinese family who are not interested in paddy and rice industry. They later sold the company to KBJS after their father’s death in 1988. KBJS bought the company at a price of RM 500, 000.00 and have been upgraded from time to time. KBJS is now well known as the biggest Bumiputera company in peninsular Malaysia according to Certified Assessment in 2011 which worth RM25 millions.